Internal medicine hospitalisations and liver disease: a comparative disease burden analysis of a multicentre cohort. Issue 5 (28th June 2021) - Roberts, Surain B.; Hansen, Bettina E.; Shin, Saeha; Abrahamyan, Lusine; Lapointe‐Shaw, Lauren; Janssen, Harry L. A.; Razak, Fahad; Verma, Amol A.; Hirschfield, Gideon M.
Summary: Background: Liver disease is an increasing burden on population health globally. Aims: To characterise burden of liver disease among general internal medicine inpatients at seven Toronto‐area hospitals and compare it to other common medical conditions. Methods: Data from April 2010 to October 2017 were obtained from hospitals participating in the GEMINI collaborative. Using these cohort data from hospital information systems linked to administrative data, we defined liver disease admissions using most responsible discharge diagnoses categorised according to international classification of diseases, 10th Revision—enhanced Canadian version (ICD‐10‐CA). We identified admissions for heart failure, chronic obstructive pulmonary disease (COPD) and pneumonia as comparators. We calculated standardised mortality ratios (SMRs) as the ratio of observed to expected deaths. Results: Among 239 018 discharges, liver disease accounted for 1.7% of most responsible discharge diagnoses. Liver disease was associated with marked premature mortality, with SMR of 8.84 (95% CI 8.06‐9.67) compared to 1.06 (95% CI 0.99‐1.12) for heart failure, 1.05 (95% CI 0.96‐1.15) for COPD and 1.28 (95% CI 1.20‐1.37) for pneumonia. The majority of deaths were among patients younger than 65 years (57.7%) compared to 3.3% in heart failure, 5.6% in COPD and 10.7% in pneumonia. Liver disease patients presented with worse Laboratory‐Based Acute Physiology Scores, were more frequently admitted to the intensive care unit (14.4%), incurred higher average total costs (median $6723 CAD), had higher in‐hospital mortality (11.4%), and were more likely to be a readmission from 30 days prior (19.8%). Non‐alcoholic fatty liver disease admissions increased from 120 in 2011‐2012 to 215 in 2016‐2017 ( P  < 0.01). Conclusion: In Canada's largest urban centre, liver disease admissions resulted in premature morbidity and mortality with higher resource use compared to common cardio‐respiratory conditions. Re‐evaluation of approaches to caring for inpatients with liver disease is timely and justified. Abstract : In Canada's largest urban centre, liver disease admissions resulted in premature morbidity and mortality with higher resource use compared to common cardio‐respiratory conditions. Liver disease patients were significantly younger, had higher in‐hospital mortality, were more frequently admitted to intensive care, incurred higher average total costs, and were more likely to be a readmission from 30 days prior. Re‐evaluation of approaches to caring for inpatients with liver disease is timely and justified.